Pengaruh latihan z-pattern run terhadap kelincahan pada siswa ekstrakurikuler sepakbola SDN Jatisampurna 10 Kota Bekasi - Fadlan, Gilang Rahman; Riyadi, Dani Nur (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2025)
The effect of Z-pattern run exercise on agility in football extracurricularstudents of SDN Jatisampurna 10 Bekasi city. The method used in this studyis an experiment with one-group pretest-posttest design. This population usesstudents of grades 4, 5 and 6. Sampling by using the technique of totalsampling with these techniques, the number of samples obtained is 25football extracurricular students of SDN Jatisampurna 10 Bekasi city. Basedon the hypothesis test of the dependent variables X and Y obtained throughthe Zig-Zag Test, the correlation of this study is supported by the results ofthe t test which shows that the value of t count (23.39) > t table (2.064). Thisstudy concluded that the Z-Pattern Run exercise method can be an effectivealternative in improving the agility of football players, especially in theschool environment.